Long-term outcomes of patients with acromegaly: a report from the Swedish Pituitary Register. Issue 3 (1st February 2022) - Arnardóttir, Steinunn; Järås, Jacob; Burman, Pia; Berinder, Katarina; Dahlqvist, Per; Erfurth, Eva Marie; Höybye, Charlotte; Larsson, Karin; Ragnarsson, Oskar; Ekman, Bertil; Edén Engström, Britt
Abstract: Objective: To describe the treatment and long-term outcomes of patients with acromegaly from all healthcare regions in Sweden. Design and methods: Analysis of prospectively reported data from the Swedish Pituitary Register of 698 patients (51% females) with acromegaly diagnosed from 1991 to 2011. The latest clinical follow-up date was December 2012, while mortality data were collected for 28.5 years until June 2019. Results: The annual incidence was 3.7/million; 71% of patients had a macroadenoma, 18% had visual field defects, and 25% had at least one pituitary hormone deficiency. Eighty-two percent had pituitary surgery, 10% radiotherapy, and 39% medical treatment. At the 5- and 10-year follow-ups, insulin-like growth factor 1 levels were within the reference range in 69 and 78% of patients, respectively. In linear regression, the proportion of patients with biochemical control including adjuvant therapy at 10 years follow-up increased over time by 1.23% per year. The standardized mortality ratio (SMR) (95% CI) for all patients was 1.29 (1.11–1.49). For patients with biochemical control at the latest follow-up, SMR was not increased, neither among patients diagnosed between 1991 and 2000, SMR: 1.06 (0.85–1.33) nor between 2001 and 2011, SMR: 0.87 (0.61–1.24). In contrast, non-controlled patients at the latest follow-up from both decades had elevated SMR, 1.90 (1.33–2.72) and 1.98 (1.24–3.14), respectively. Conclusions: The proportion of patients with biochemical control increased over time. Patients with biochemically controlled acromegaly have normal life expectancy, while non-controlled patients still have increased mortality. The high rate of macroadenomas and unchanged age at diagnosis illustrates the need for improvements in the management of patients with acromegaly.